Risk Factors for Poor Postoperative Outcome and Epileptic Symptoms in Patients Diagnosed with Cerebral Cavernous Malformations - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Roessler, Karl (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Objective Roughly 12 to 47% of individuals with cerebral cavernous malformations (CCM) are asymptomatic, while other people may present with symptoms such as epileptic seizures, neurologic deficits, and intracerebral hemorrhages (IH). The aim of this study was to report our experience of postoperative outcomes of patients diagnosed with CCMs.Patients and Methods We present a series of consecutive patients who underwent surgical treatment for a diagnosed CCM between January 2003 and March 2014. Data were retrospectively analyzed with respect to preoperative visits, operating reports, patient admission charts, and postoperative follow-up visits. The Engel scale was used to evaluate the outcome of patients with epileptic seizures.Results A total of 91 patients were included with a mean age of 38.8 ± 15 years (range: 2–72 years). Prior to surgery, 57 of these patients had epileptic seizures, while 25 patients recorded at least one episode of IH with a latency time of 6.7 ± 8.5 years (range: 3–240 months) in between hemorrhages. A CCM located within the brainstem was significantly associated with IH prior to surgery (p = 0.000). If the CCM was adjacent to an eloquent brain area, the postoperative outcome in terms of seizure control was significantly worse (p = 0.033). In addition, a trend for worsened outcomes according to the Engel scale was observed in patients with more than one seizure prior to surgery (p = 0.055).Conclusion Proximity of CCMs to eloquent brain areas is a risk factor for poor postoperative outcome with respect to a lower rate of medication reduction as well as a lower rate of epileptic seizure omission. This underlines the importance of patient-specific therapeutic approaches.
Keywords: cerebral cavernous malformation; cavernoma; outcome; epileptic symptoms